The Remezov chronicle’s story “On the ancient prophecy” in the context of the ideological constructions of Russian scribes - Lyapin D.A. (Золотоордынское обозрение)
The purpose of the study: To demonstrate the ideological justification for the annexation of Siberia to Russia in the story of the Remezov Chronicle, “On the Ancient Prophecy”, associated both with the traditional motive of revenge for violation of borders by the Tatars, and with fundamentally new reasoning that corresponds to the historical situation of the late 17th century. Research materials: Siberian chronicles of the 17th century: Esipov Chronicle, Stroganov Chronicle, Remezov Chronicle. The main place is occupied by the story found in the Remezov Chronicle about the “Ancient prophecy”. Results and novelty of the research: Russia’s advance into Siberia in the 17th century had pragmatic economic grounds, but the Siberian chronicles were obliged to have shown other, more sublime reasons. The first Siberian chronicles believed that the reasons for Russian successes were Divine Providence, and the invasion of military detachments was associated with the need to conduct missionary work. But only the Remezov Chronicle of the late 17th century first offered the reader logical reasons for the need to conquer the vast, rich lands of Siberia. Without denying the factor of Divine agency, there was a traditional motive of revenge on the Tatars for violating sacred borders during the invasion of the 13th century. The Russians took revenge for the Tatar yoke. This idea of sacred boundaries is very early for Russian literature. The destruction of the Siberian kingdom of Kuchum by the Cossacks was a logical aim in Moscow’s fight against the Horde. The original idea was mainly framed as the need to conquer Siberia to prevent a new Mongol-Tatar invasion.